Determination of vanadium in Natural gas using graphite furnace atomic absorption spectrometry (GFAAS) - Suham Tawfiq; Abdul Majeed Khursheed; Tuana Abdulla (College of Education for Pure Sciences, 2013)
ABSTRACT Vanadium is recognized worldwide as the most abundant metallic constituent in petroleum, and this led to expect of its existing in natural gas that associated with oil as a trace amount in ppb concentration or less. For capturing the trace amount of vanadium in natural gas we used diluted acidic medium as adsorption collection, and using the collection medium as a sample. Graphite furnace atomic absorption spectrometry (GFAAS) is the analytical method that utilized in this study to determine (nano-partical) of vanadium. The pyrolysis and atomization temperature used were 1100ᵒC and 2700ᵒC , respectively. This procedure allows determination of vanadium with a detection limit about 0.44µg/L and characteristic mass of 67 pg, the calibration graph was linear in the range (40-120)µg/L with correlation coefficient of 0.9980, and the relative standard deviation RSD% was (0.83-6.13). the accuracy of this procedure was confirmed by the determination of vanadium in a newly prepared standard solution as unknown concentration. The range of vanadium amount in natural gas supposed to be from 5-10 ng/L .